Tantangan Globalisasi terhadap Penerapan Konsep Falah dalam Ekonomi Islam - Fakhrezi Wildan Hrp; Falih Arkan Hasibuan; M. Hanif Abrar; Ahmad Wahyudi Zein (STIKes Ibnu Sina Ajibarang, 2025)
This article discusses the complexity of the challenges faced by Islamic economics in the evolving context of globalization. Using a qualitative research method based on a literature review, this article identifies and analyzes various factors that influence the application of the concept of falah, which means prosperity and success in the Islamic economic system. In the era of globalization, Islamic economics must face several major challenges, including; facing difficulties in integrating Islamic values with global economic practices that tend to be capitalist, the need to create competitive products and services in accordance with sharia principles, the need for a regulatory framework that supports the development of Islamic economics in order to compete in the global market, increasing public understanding of the principles of Islamic economics and its benefits. This article concludes that to overcome these challenges, a collaborative strategy is needed between the government, Islamic financial institutions, academics and the community. With an integrated approach, Islamic economics can capitalize on opportunities in a dynamic global economic system and has the potential to become a sustainable and inclusive alternative.